Investigating the Variation of Corrugated Board Properties - Preeti Sharma; Mohit Kumar; Abhishek Saini (Current Overview on Science and Technology Research Vol. 7, 2022)
Corrugated packaging is intended to meet the needs of product protection, material efficiency, and environmental impact. The goal of this paper is to investigate the variations in corrugated board properties and then provide solutions to improve the board’s properties. We discovered opportunities to solve the variation in corrugation board properties for this study. In this study, numerous varieties of paper and paperboard with varying GSM, thickness, bursting strength, and cobb values were investigated. Cobb value determines the amount of water or any Liquid absorbed by the board in a given period of time under some conditions. The high cobb value of board indicates the ability of material to retain or absorb moisture. This kind of board, also known as corrugated board, is perfect for packing since it is lightweight and protects the environment, among other things.